PERENCANAAN KEBUTUHAN SISTEM INFORMASI PADA BAGIAN KEUANGAN PT PERKEBUNAN NUSANTARA XI - rakhman, febrian abindra; Tanuwijaya, Haryanto; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
This research is motivated by the problems that arise in the financial departement of Perkebunan Nusantara XI Corp associated with the use of information systems in its operational activities. The use of current information systems have the purpose of facilitating the operations of finance in order to save the cost of operational expenses. But their current information systems lead to swelling operating costs and investments is not reached. This research aims to create a site planning information system needs on the financial department of Perkebunan Nusantara XI Corp corresponding to the operations of the financial department. In completing the objectives of this study will be used method of Ward and Peppard. In the method of Ward and Peppard to do financial business analysis and information technology systems before planning information system requirements for the finance department. The results of this study form part of the financial application portfolio that can be built within one year two months.